DEVELOPING VIDEO AS THE TEACHING MEDIA OF WRITING DESCRIPTIVE TEXT FOR GRADE VIII STUDENTS IN SMP BRIGJEND. KATAMSO 1 MEDAN - Br. Karo, Meyke Pratiwi; Sumarsih, Sumarsih; Erlita, Yeni (TRANSFORM: Journal of English Language Teaching and Learning, 2019)
This research was aimed to develop video as the teaching media of writing descriptive text for grade VIII students in SMP Brigjend.Katamso I Medan. This study was categorized as Research and Development (R & D) study which adapted from Borg and Gall (2003). The method through six phases: conducting need analysis, designing, developing, experts validating, revising, and final product. The subjects of this research were 40 students of grade eighth of SMP Brigjend. Katamso I Medan which was located in Jl. Sunggal No. 370 Medan. The data and data resources were the teacher™s lesson plan, teacher™s interview, and students™ questionnaires result. After getting the last data, the media should be planned to be designed as the students™ needs. The media were developed and had been validated by the experts. The percentages of the media from the experts were 90% that categorized as very good. It can be concluded that video as one of the creative media to improve the students™ ability in writing descriptive texts.Key words: Research and development (R&D),Descriptive Text, Video, Writing, Junior High School.